2021
DOI: 10.14202/ijoh.2021.12-18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Schistosoma japonicum infection in water buffaloes in selected areas in Davao del Norte and Davao de Oro, the Philippines

Abstract: Background and Aim: Schistosomiasis (SCH) japonica is a zoonotic disease that can infect several mammalian hosts. Bovines, particularly water buffaloes, are considered the most important reservoir hosts due to the high levels of schistosome eggs, they excrete into the environment. In the Philippines, the previous studies have revealed a high prevalence of SCH in bovines in selected provinces in Luzon, Visayas, and Mindanao. However, there is a lack of studies on SCH in the Davao Region, Mindanao, where the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A recent study in South Cotabato showed that 48.6% of cattle and 60.5% of water buffaloes were positive for the infection using FEA-SD technique [42]. Another recent study revealed that 8.6% of sampled water buffaloes in Maragusan, Davao de Oro, were positive for schistosomiasis japonica [43]. As mentioned above, schistosomiasis japonica was also noted in other mammalian reservoir hosts [29][30][31][32].…”
Section: Veterinary Public Healthmentioning
confidence: 88%
“…A recent study in South Cotabato showed that 48.6% of cattle and 60.5% of water buffaloes were positive for the infection using FEA-SD technique [42]. Another recent study revealed that 8.6% of sampled water buffaloes in Maragusan, Davao de Oro, were positive for schistosomiasis japonica [43]. As mentioned above, schistosomiasis japonica was also noted in other mammalian reservoir hosts [29][30][31][32].…”
Section: Veterinary Public Healthmentioning
confidence: 88%
“…These findings indicate that the prevalence rates of schistosomiasis can vary even in endemic areas, as highlighted in an extensive review by Tenorio et al [84]. It is argued that the low prevalence reported in some studies could also be a result of the poor sensitivity of the tests used for stool analysis and can be improved by adjusting the FEA-SD protocol used and utilizing more sensitive techniques such as the polymerase chain reaction (PCR) tests [72,83]. It is, however, necessary to ascertain the impact of a transmission-blocking vaccine in these regions, as livestock animals, particularly water buffalo, are allowed to graze in contaminated fields.…”
Section: Rationale and Implications For The Development Of A Veterina...mentioning
confidence: 96%
“…It is interesting to note the variation in prevalence rates of schistosomiasis in different host animals in the Philippines. The prevalence rate of S. japonicum in water buffalo in the Philippines was previously reported to be low or even absent, and it was thought that rodents and canines were the main reservoir hosts for schistosomiasis transmission, having higher prevalence rates than water buffalo [31,[80][81][82][83]. In fact, the prevalence rates of schistosomiasis in rodents were reported to be as high as 73%, while dogs had up to 19% [80,81,84].…”
Section: Rationale and Implications For The Development Of A Veterina...mentioning
confidence: 99%
“…Furthermore, prevalence of schistosomiasis in bovines in known endemic areas is as high as 90%. It is now believed that animal reservoir hosts, especially carabaos, are important drivers of transmission in these areas [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%